Ciberativismo nas redes sociais : um estudo do Movimento Brasil Livre no pós-impeachment de Dilma Rousseff - Tonetto, Mauricio Bozzi (2018)
Through a study of the Brazilian Free Movement (MBL) in the post-impeachment of Dilma Rousseff, this dissertation analyzes political activism in virtual social networks – cyberactivism. The MBL was notable in 2015 and 2016 for commanding protests that took millions of people to the streets and influenced the fall of the Workers’ Party (PT) of the Presidency of the Republic. The main objectives of this work are to understand how cyberactivism becomes institutionalized in politics, how the group acts after impeachment and how Brazilian cyberactivism has moved from guerrilla to industrialization with MBL. A total of 102 publications of the fanpage of the movement on Facebook are analyzed in three periods of 2017: in the two accusations of Justice against the President of the Republic, Michel Temer, for corruption and other crimes; and the acquittal of Senator Aécio Neves of the PSDB by his parliamentary colleagues who rejected a decision of the Federal Supreme Court (STF) that had removed him from the National Congress for attempting to obstruct Justice in Operation Lava Jato. The method applied was Discursive Textual Analysis, which resulted in metatexts that synthesize the core of the cyberactivism practiced by MBL. We discussed the transformations of cyberspace, the characteristics of the new networked society, virtual social networks and the rise of cyberactivism, as well as topics such as filter bubbles, obscure algorithms, fake news and internet monopoly. Ciberativism, which emerges in tune with the ideal of independence and freedom sought by the creators of the internet, is also an instrument for the propagation of hatred, manipulation and lies, and for the intensification of radicalisms, thus occupying a central role in cyberculture studies and social movements.